KNOWLEDGE AND PRACTICE OF NURSES REGARDING CHEST DRAIN MANAGEMENT - AHMAD , S; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Chest drain management is a vital component of critical care nursing, requiring comprehensive knowledge and adherence to evidence-based practices. In resource-limited settings like Pakistan, gaps in nursing competencies pose challenges to patient safety and outcomes. This study aimed to assess the knowledge and practices of ICU nurses regarding chest drain management in tertiary care hospitals. Methods: A descriptive cross-sectional study was conducted among 120 ICU nurses in Lahore, Pakistan. Participants were selected using convenience sampling. Data were collected through a validated structured questionnaire covering demographic information, knowledge, and practices. Statistical analysis was performed using SPSS version 26, employing descriptive and inferential statistics. Results: While 90.6% of nurses demonstrated correct knowledge about chest drain insertion sites, only 11.1% were aware of specific indications such as pneumothorax and hemothorax. Infection prevention practices were inadequate, with only 13.7% adhering to proper protective measures. Practices such as patient positioning and dressing changes were also suboptimal, with adherence rates of 10.3% and 7.7%, respectively. Advanced qualifications and greater experience were associated with higher competency levels (p < 0.05). Conclusion: The study identified significant gaps in knowledge and practices related to chest drain management among ICU nurses in Pakistan. Targeted training programs, competency assessments, and enhanced institutional policies are essential to address these deficiencies, improve patient outcomes, and ensure adherence to international standards in critical care nursing.